COMMUNITY EMPOWERMENT IN ECONOMIC DEVELOPMENT IN SIDOARJO - Zaki, Talitha Nabilah; Kamil, Muhammad; Salahudin, Salahudin (DIA: Jurnal Administrasi Publik, 2022)
The purpose of this study is to describe the role of government and non-government in community economic empowerment as well as to alert the supporting and inhibiting factors that link the economic empowerment of the community in Kebonsari Village, Candi District, Sidoarjo Regency. There are many challenges faced by the government and the community who want or have ideas, for example, community empowerment to improve the economy for local residents and can become a pilot area for other regions in order to provide ideas for other opportunities to empower unemployed citizens to have their own stage. This research method uses a review paper using a research vosviewer, which reveals that the government policy of Sidoarjo Regency in community members, especially duck breeders in Kebonsari Village, Candi District, includes providing livestock assistance and facilitating facilities and infrastructure for duck breeders, as well as an extension of the Government. In fostering, directing and controlling including opening market opportunities, especially outside the regional market and also being able to improve the economy of Sidoarjo residents by empowering or providing ideas for business opportunities that can be utilized by the community and Sidoarjo residents themselves. With support from the government, the government provides facilities that can be used by the community. In addition, the facilities provided by the government are intended to get assistance from the banking sector, so that the community empowerment activities for duck farming groups are established. The limitation of this research is that journals and articles only use the Scopus data base. However, to overcome these limitations, the next research can also use other data bases.